2022
DOI: 10.3233/jad-215290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Microbiota-Gut-Brain Axis on Cognition in Alzheimer’s Disease

Abstract: The gut microbiota is made up of trillions of microbial cells including bacteria, viruses, fungi, and other microbial bodies and is greatly involved in the maintenance of proper health of the host body. In particular, the gut microbiota has been shown to not only be involved in brain development but also in the modulation of behavior, neuropsychiatric disorders, and neurodegenerative diseases including Alzheimer’s disease. The precise mechanism by which the gut microbiota can affect the development of Alzheime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…Moreover, germ-free mice have an abnormal response to stress, which can be normalized by recolonizing them with a complete microbiota (via stool transplant) or by monocolonization with Bifidobacterium Infantis [59]. It is now well recognized that GM can affect the integrity and the diverse functions of CNS including regulation of the mood and cognition [60][61][62][63].…”
Section: Gut-brain Axis (Gba)mentioning
confidence: 99%
“…Moreover, germ-free mice have an abnormal response to stress, which can be normalized by recolonizing them with a complete microbiota (via stool transplant) or by monocolonization with Bifidobacterium Infantis [59]. It is now well recognized that GM can affect the integrity and the diverse functions of CNS including regulation of the mood and cognition [60][61][62][63].…”
Section: Gut-brain Axis (Gba)mentioning
confidence: 99%
“…This allows the identification of pathways that regulate BGM signaling between the digestive tract and the brain, including neural, endocrine, and immune pathways. It has been shown that the BGM axis plays an important role in the formation and maintenance of cognitive functions [ 16 , 17 , 18 , 19 ]. Moreover, the BGM axis was proved to be significant in the regulation of neurogenesis, one of the most essential processes of proliferation, migration, and differentiation of new neural cells [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the intriguing adaptive response to exercise training involves gut microbiome. The gut-brain axis has been proposed signi cantly interferes with the function of both organs and more and more data suggest that the microbiome of gut has a powerful effect in gut-brain axis (7,8). Clinical trial showed that Bi dobacterium bi dum and Bi dobacterium longum containing postbiotics caused changes in gut microbiota and promoted mental exibility, alleviated stress in healthy older adults, along with causing changes in gut microbiota (9).…”
Section: Introductionmentioning
confidence: 99%